Quo vadis ”історіє повсякдення”? - Куновська, О. (Інститут історії України НАН України, 2008)
У статті представлено основні витоки до формування наукового напряму «історія повсякдення». Основу аналізу становлять праці західних науковців, трьох «шкіл»: німецької «Альтагсгешіште», італійської «мікросторіа», французької «іствар дю котідієн» на базі наукових творінь яких і сформувалися основні теми, предмет, методологія дослідження історій щоденного життя сьогодні. Крім того, розглядається поширення «історії повсякдення» у східноєвропейський простір і зміну тенденцій у написанні такого виду історій. The article is dedicated to the “history of everyday life”, – one of the most promising trends in the contemporary historiography. At presents the works of Western scholars of three „schools”, such as German Alltagsgeschichte, Italian microstoria, French histoire du quotidien, on the basis of which the main themes, subjects, methodology of the research of everyday life history were created. Besides, in the article one can find the references to the works of scholars, who come from and study the Central and Eastern Europe, as well as the outline of changes in the tendencies of writing such a type of history and its further prospects.